Method for controlling inclusions of stainless steel microwires for silk-screen printing of photovoltaic cells

By adjusting the alkalinity of the slag and adding synthetic slag in a vacuum oxygen-blowing decarbonization furnace, the Al content in the stainless steel microfilament was controlled, and the wire breakage problem caused by stainless steel microfilament inclusions in the screen printing of photovoltaic cells was solved, achieving high The effect of cleanliness and mechanical strength.

CN119410863APending Publication Date: 2025-02-11HAIWEI SILK SCREEN PRINTING MATERIALS (JIANYIN) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411597439.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The stainless steel microwires used for screen printing of photovoltaic cells are prone to inclusions or hard particles of more than 5 μm during the cold drawing process, resulting in broken wires and high cleanliness requirements.

Method used

By using low aluminum-ferrosilicon reduction in vacuum oxygen-blown decarbonization furnace and adjusting the alkalinity of the slag ≥2.1, adding synthetic slag to adjust the alkalinity of the slag to 1.5 to 1.9, and the Al content in the control steel is less than 0.004 wt%. To ensure plasticization of inclusions.

Benefits of technology

It is achieved to ensure the cleanliness and mechanical strength of the stainless steel microwires with less oxygen and sulfur increase, and avoid wire breakage problems caused by inclusions.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a method for controlling inclusions of stainless steel microfilaments for silk-screen printing of photovoltaic cells, which comprises the following steps of: S1, reducing in a vacuum oxygen blowing decarburization furnace by adopting low-aluminum silicon iron, adjusting the alkalinity of slag to be greater than or equal to 2.1, and adding slag charge to adjust the flowability of the slag; and S2, after the reduction period of the vacuum oxygen blowing decarburization furnace, synthetic slag is added, the alkalinity of the slag is adjusted to 1.5-1.9, the content of alkali metal compounds in the slag is 2-8 wt%, and the content of Al in steel is lower than 0.004 wt%. The inclusions are regulated and controlled through the slag instead of adding alloy, the adding process is more controllable and simpler, and the method is suitable for various process routes and easier to popularize in large-scale industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal material processing, in particular to a method for controlling stainless steel microwire inclusions for photovoltaic cell screen printing. Background Art

[0002] The ultra-high-strength stainless steel microwire used for photovoltaic cell screen printing has the characteristics of high strength, high tension and high dimensional accuracy, which is very suitable for precision printing. Compared with other steel mesh materials, ultra-high-strength stainless steel microwire can be used with finer wire diameters, which makes it have greater advantages in plate making and can print higher-quality patterns. At the same time, its high strength also ensures stability and durability during the printing process.

[0003] In order to ensure that stainless steel microwires have sufficient mechanical strength and corrosion resistance, there are strict upper limits on the TO content and S content. Inclusions or hard spots larger than 5μm during cold drawing will cause wire breakage. Compared with cord steel, cutting wire, spring steel, etc., microwire stainless steel has higher requirements on cleanliness, especially the plasticity of inclusions.

[0004] Therefore, it is desired to provide a method for controlling inclusions in stainless steel microwires for screen printing of photovoltaic cells, which can solve the above technical problems. Summary of the invention

[0005] The purpose of the present invention is to provide a method for controlling inclusions of stainless steel microwires for screen printing of photovoltaic cells. A slag basicity lower than 1.6 will lead to a substantial increase in TO and S in the steel and poor cleanliness. The present invention ensures the plasticization of inclusions under less oxygen and sulfur addition conditions.

[0006] In order to achieve the above-mentioned purpose of the invention, a method for controlling inclusions in stainless steel microwires for screen printing of photovoltaic cells is provided, comprising the following steps:

[0007] S1. Use low-aluminum ferrosilicon reduction in a vacuum oxygen decarburization furnace, adjust the basicity of the slag to ≥2.1, and add slag to adjust the fluidity of the slag;

[0008] S2. After the reduction period of the vacuum oxygen decarburization furnace, synthetic slag is added to adjust the basicity of the slag to 1.5-1.9, and the content of alkali metal compounds in the slag is 2-8wt%, and the Al content in the steel is less than 0.004wt%.

[0009] Preferably, in step S1, oxygen is blown from the oxygen lance on the top of the vacuum oxygen decarburization furnace, at which time silicon is first oxidized, and then carbon is oxidized. When a predetermined temperature and silicon content are reached in the vacuum oxygen decarburization furnace, carbon monoxide begins to be generated and decarburization begins.

[0010] Preferably, in step S1, in a vacuum oxygen decarburization furnace, the CO:CO2 value in the furnace is monitored, and when the carbon content in the molten pool reaches 0.075%, oxygen blowing is stopped, the pressure in the furnace is reduced, argon is blown for stirring, and then reducing silicon, lime and fluorite are added in sequence for desulfurization.

[0011] Preferably, in terms of weight percentage, the synthetic slag comprises 50% to 58% CaO, 28% to 36% Al2O3, 6% to 8% SiO2, 7% to 9% MgO, and ≤6% CaF2.

[0012] Furthermore, the particle size of the synthetic slag is 5 to 40 mm.

[0013] Furthermore, after step S2, step S3 of heat treatment is also included, firstly, the product treated in step S2 is heated to 900° C. and kept at this temperature for 20 to 30 minutes; then, it is heated to 1000° C. and kept at this temperature for 60 to 80 minutes before being taken out for quenching.

[0014] Specifically, the quenching is performed by water quenching.

[0015] Furthermore, the content of Al and Ti in the low-aluminum ferrosilicon is less than 0.7wt%.

[0016] Further, in step S3, the steel is heated to 900° C. at a heating rate of 5 to 8° C. per minute and kept at this temperature for 20 to 30 minutes; then heated to 1000° C. and kept at this temperature for 60 to 80 minutes before being taken out for quenching.

[0017] Furthermore, after step S3, scanning analysis is also included, in which a scanning electron microscope is used to scan the surface of the sample point by point and line by line to obtain the crystallographic orientation of each point in the micro-region.

[0018] Compared with the prior art, the method for controlling inclusions of stainless steel microwires for screen printing of photovoltaic cells of the present invention has the following advantages:

[0019] (1) Inclusions are regulated by slag rather than by alloy addition, which makes the addition process more controllable and simple, applicable to a variety of process routes, and easier to promote in large-scale industrial production;

[0020] (2) Develop ultra-high purity austenitic stainless steel micro-wire smelting technology to achieve industrial production of high homogeneity wire rods;

[0021] (3) The production process is simplified and highly efficient and energy-saving. DETAILED DESCRIPTION

[0022] The present invention is further described below in conjunction with specific embodiments.

[0023] Example 1

[0024] A method for controlling inclusions of stainless steel microwires for screen printing of photovoltaic cells in this embodiment comprises the following steps:

[0025] S1. Use low-aluminum ferrosilicon reduction in a vacuum oxygen decarburization furnace, adjust the basicity of the slag to ≥2.1, and add slag to adjust the fluidity of the slag;

[0026] S2. After the reduction period of the vacuum oxygen decarburization furnace, synthetic slag is added to adjust the basicity of the slag to 1.5, and the content of alkali metal compounds in the slag is 2-8wt%, and the Al content in the steel is less than 0.004wt%.

[0027] Among them, in step S1, oxygen is blown from the oxygen gun on the top of the vacuum oxygen decarburization furnace. At this time, silicon is first oxidized, and then waits for carbon to be oxidized. When the predetermined temperature and silicon content are reached in the vacuum oxygen decarburization furnace, carbon monoxide begins to be generated and decarburization begins.

[0028] Further in this embodiment, in step S1, in the vacuum oxygen decarburization furnace, the CO:CO2 value in the furnace is monitored. When the carbon content in the molten pool reaches 0.075%, oxygen blowing is stopped, the pressure in the furnace is reduced, argon is blown for stirring, and then reducing silicon, lime and fluorite are added in sequence for desulfurization.

[0029] In this embodiment, the synthetic slag includes, by weight percentage, CaO 50%, Al 2 O 3 30%, SiO 28%, MgO 9%, and CaF 23%.

[0030] In this embodiment, the particle size of the synthetic slag is 5 mm.

[0031] Example 2

[0032] A method for controlling inclusions of stainless steel microwires for screen printing of photovoltaic cells in this embodiment comprises the following steps:

[0033] S1. Use low-aluminum ferrosilicon reduction in a vacuum oxygen decarburization furnace, adjust the basicity of the slag to ≥2.1, and add slag to adjust the fluidity of the slag;

[0034] S2. After the reduction period of the vacuum oxygen decarburization furnace, synthetic slag is added to adjust the basicity of the slag to 1.5-1.9, and the content of alkali metal compounds in the slag is 2-8wt%, and the Al content in the steel is less than 0.004wt%.

[0035] In this embodiment, in step S1, oxygen is blown from the oxygen lance on the top of the vacuum oxygen decarburization furnace. At this time, silicon is first oxidized, and then the carbon is oxidized. When the predetermined temperature and silicon content are reached in the vacuum oxygen decarburization furnace, carbon monoxide begins to be generated and decarburization begins.

[0036] Furthermore, in this embodiment, in step S1, in the vacuum oxygen decarburization furnace, the CO:CO2 value in the furnace is monitored, and when the carbon content in the molten pool reaches 0.075%, oxygen blowing is stopped, the pressure in the furnace is reduced, argon is blown for stirring, and then reducing silicon, lime and fluorite are added in sequence for desulfurization.

[0037] In this embodiment, the synthetic slag includes, by weight percentage, 50% CaO, 30% Al2O3, 27% SiO, 8% MgO, and 25% CaF.

[0038] In this embodiment, the particle size of the synthetic slag is 10 mm.

[0039] In this embodiment, after step S2, step S3 of heat treatment is further included, firstly, the product treated in step S2 is heated to 900°C and kept at this temperature for 25 minutes, then heated to 1000°C and kept at this temperature for 70 minutes before being taken out for quenching. The quenching is performed by water quenching.

[0040] Example 3

[0041] A method for controlling inclusions of stainless steel microwires for screen printing of photovoltaic cells in this embodiment comprises the following steps:

[0042] S1. Use low-aluminum ferrosilicon reduction in a vacuum oxygen decarburization furnace, adjust the basicity of the slag to ≥2.1, and add slag to adjust the fluidity of the slag;

[0043] S2. After the reduction period of the vacuum oxygen decarburization furnace, synthetic slag is added to adjust the basicity of the slag to 1.5-1.9, and the content of alkali metal compounds in the slag is 2-8wt%, and the Al content in the steel is less than 0.004wt%.

[0044] Among them, in step S1, oxygen is blown from the oxygen gun on the top of the vacuum oxygen decarburization furnace. At this time, silicon is first oxidized, and then waits for carbon to be oxidized. When the predetermined temperature and silicon content are reached in the vacuum oxygen decarburization furnace, carbon monoxide begins to be generated and decarburization begins.

[0045] Among them, in step S1, in the vacuum oxygen decarburization furnace, the CO:CO2 value in the furnace is monitored. When the carbon content of the molten pool reaches 0.075%, the oxygen blowing is stopped, the pressure in the furnace is reduced, argon is blown for stirring, and then reducing silicon, lime and fluorite are added in sequence for desulfurization.

[0046] Wherein, by weight percentage, the synthetic slag includes 52% CaO, 35% Al2O3, 26% SiO, 7% MgO and 22% CaF.

[0047] In this embodiment, the particle size of the synthetic slag is 20 mm.

[0048] In this embodiment, after step S2, step S3 heat treatment is also included. First, the product treated in step S2 is heated to 900°C and kept warm for 30 minutes; then heated to 1000°C, kept warm for 80 minutes, and then taken out for quenching. The quenching is performed by water quenching.

[0049] In this embodiment, the content of Al and Ti in the low-aluminum ferrosilicon is less than 0.7wt%.

[0050] Among them, in step S3, the heating rate is increased by 56°C per minute to 900°C, and the temperature is kept for 20 minutes; then it is heated to 1000°C, kept for 60 minutes, and then taken out for quenching.

[0051] Example 4

[0052] A method for controlling inclusions of stainless steel microwires for screen printing of photovoltaic cells in this embodiment comprises the following steps:

[0053] S1. Use low-aluminum ferrosilicon reduction in a vacuum oxygen decarburization furnace, adjust the basicity of the slag to ≥2.1, and add slag to adjust the fluidity of the slag;

[0054] S2. After the reduction period of the vacuum oxygen decarburization furnace, synthetic slag is added to adjust the basicity of the slag to 1.5-1.9, and the content of alkali metal compounds in the slag is 2-8wt%, and the Al content in the steel is less than 0.004wt%.

[0055] Among them, in step S1, oxygen is blown from the oxygen gun on the top of the vacuum oxygen decarburization furnace. At this time, silicon is first oxidized, and then waits for carbon to be oxidized. When the predetermined temperature and silicon content are reached in the vacuum oxygen decarburization furnace, carbon monoxide begins to be generated and decarburization begins.

[0056] Among them, in step S1, in the vacuum oxygen decarburization furnace, the CO:CO2 value in the furnace is monitored. When the carbon content of the molten pool reaches 0.075%, the oxygen blowing is stopped, the pressure in the furnace is reduced, argon is blown for stirring, and then reducing silicon, lime and fluorite are added in sequence for desulfurization.

[0057] Preferably, the synthetic slag comprises, by weight percentage, 53% CaO, 28% Al2O3, 26% SiO, 7% MgO, and 26% CaF.

[0058] Wherein, the particle size of the synthetic slag is 40 mm.

[0059] In this embodiment, after step S2, step S3 of heat treatment is further included, firstly, the product treated in step S2 is heated to 900°C and kept at this temperature for 30 minutes, then heated to 1000°C and kept at this temperature for 80 minutes before being taken out for quenching. Specifically, the quenching is performed by water quenching.

[0060] Wherein, the content of Al and Ti in the low-aluminum ferrosilicon is less than 0.7wt%.

[0061] Among them, in step S3, the heating rate is 8°C per minute to 900°C, and the temperature is kept for 30 minutes; then it is heated to 1000°C, kept for 60 minutes, and then taken out for quenching.

[0062] After step S3, scanning analysis is also included, in which the surface of the sample is scanned point by point and line by line using a scanning electron microscope to obtain the crystallographic orientation of each point in the micro-region.

[0063] The slag inclusion determination method of the products prepared in Examples 1 to 4 is as follows: referring to the ASTM E45 standard, the test results show that the residual amount of the residue in Examples 1 to 4 is very small, and the hardness of the stainless steel is tested at the same time, and the hardness is: HV 220. The intergranular corrosion requirements of the stainless steel are tested, and the test is qualified according to the ASTM A262 standard.

[0064] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for controlling inclusions in stainless steel microwires for screen printing of photovoltaic cells, characterized in that: The following steps are included: S1. Use low-aluminum ferrosilicon reduction in a vacuum oxygen decarburization furnace, adjust the basicity of the slag to ≥2.1, and add slag to adjust the fluidity of the slag; S2. After the reduction period of the vacuum oxygen decarburization furnace, synthetic slag is added to adjust the basicity of the slag to 1.5-1.9, and the content of alkali metal compounds in the slag is 2-8wt%, and the Al content in the steel is less than 0.004wt%.

2. A method for controlling inclusions in stainless steel microwires for screen printing of photovoltaic cells as claimed in claim 1, characterized in that: In step S1, oxygen is blown from the oxygen lance on the top of the vacuum oxygen decarburization furnace. At this time, silicon is first oxidized, and then carbon is oxidized. When the predetermined temperature and silicon content are reached in the vacuum oxygen decarburization furnace, carbon monoxide begins to be generated and decarburization begins.

3. A method for controlling inclusions in stainless steel microwires for screen printing of photovoltaic cells as claimed in claim 1 or 2, characterized in that: In step S1, in a vacuum oxygen decarburization furnace, the CO:CO2 value in the furnace is monitored. When the carbon content in the molten pool reaches 0.075%, oxygen blowing is stopped, the pressure in the furnace is reduced, argon is blown for stirring, and then reduced silicon, lime and fluorite are added in sequence for desulfurization.

4. A method for controlling inclusions in stainless steel microwires for screen printing of photovoltaic cells as claimed in claim 1, characterized in that: Calculated by weight percentage, the synthetic slag includes CaO 50% to 58%, Al2O3 28% to 36%, SiO2 6% to 8%, MgO 7% to 9%, and CaF2 ≤ 6%.

5. A method for controlling inclusions in stainless steel microwires for screen printing of photovoltaic cells as claimed in claim 4, characterized in that: The particle size of the synthetic slag is 5 to 40 mm.

6. A method for controlling inclusions in stainless steel microwires for screen printing of photovoltaic cells as claimed in claim 1, characterized in that: After step S2, the method further includes step S3 of heat treatment, firstly heating the product after the treatment in step S2 to 900° C. and keeping the temperature for 20 to 30 minutes; then heating the product to 1000° C. and keeping the temperature for 60 to 80 minutes before taking it out for quenching.

7. A method for controlling inclusions in stainless steel microwires for screen printing of photovoltaic cells as claimed in claim 6, characterized in that: The quenching is done by water quenching.

8. A method for controlling inclusions in stainless steel microwires for screen printing of photovoltaic cells as claimed in claim 7, characterized in that: The contents of Al and Ti in the low-aluminum ferrosilicon are less than 0.7 wt %.

9. A method for controlling inclusions in stainless steel microwires for screen printing of photovoltaic cells as claimed in claim 6, characterized in that: In step S3, the steel is heated to 900°C at a heating rate of 5-8°C per minute and kept at this temperature for 20-30 minutes; then heated to 1000°C and kept at this temperature for 60-80 minutes before being taken out for quenching.

10. A method for controlling inclusions in stainless steel microwires for screen printing of photovoltaic cells as claimed in claim 6, characterized in that: After step S3, scanning analysis is also included, in which the surface of the sample is scanned point by point and line by line using a scanning electron microscope to obtain the crystallographic orientation of each point in the micro-region.